Recovery of knee function after total knee arthroplasty: different outcomes in patients with osteoarthritis and rheumatoid arthritis - Reiß, Lena; Stolle, Jeska; Carl, Hans-Dieter; Swoboda, Bernd (Zeitschrift für Rheumatologie, 2014)
Following total knee arthroplasty (TKA), no investigations have been published to assess possible differences between rheumatoid arthritic (RA) and osteoarthritic (OA) patients with respect to patient-reported outcome measures of knee function.A cohort of 128 consecutively operated patients (OA: n = 92, RA: n = 36) treated with bicondylar TKA was included in this prospective, clinical study. Knee function was assessed preoperatively and at 6 and 12 months after TKA, using the Knee Injury and Osteoarthritis Outcome Score (KOOS) and Oxford Knee Score (OKS).Both OKS and KOOS revealed a statistically significant improvement for OA and RA patients at 6 and 12 months after surgery, as compared to the preoperative status. The results of the OKS at 6 and 12 months did not show a further improvement for either group. The KOOS, however, revealed an additional improvement between 6 and 12 months for the osteoarthritis group, regarding the total score and all subscores, but not for the RA subgroup.Functional recovery after TKA improves in the second 6 months after surgery in OA patients, but not in RA patients, when knee function is exclusively assessed with patient-reported outcome measures.
EVALuna2:10896